Health Status and Mammography Use Among Older Women - Burack, Robert C (Blackwell Science Inc, 1998)
OBJECTIVE: To assess the extent to which an age-associated reduction in mammography use can be explained by declining self-reported health status. DESIGN: We analyzed data from the 1992 National Health Interview Survey (NHIS) and Cancer Control Supplement. Logistic regression analysis was used to evaluate the association between age, health status (self-reported health and limitations in major activity), and other variables potentially related to mammography use within the past 1 year (recent mammography). PARTICIPANTS: Of 12,035 NHIS respondents we restricted our analysis to the 1,772 women aged 50 years or older who reported one or more lifetime mammograms. We excluded women without a mammogram (n = 937) because we were interested in factors related to recent use versus past use of mammography. MEASUREMENTS AND MAIN RESULTS: The percentage of women with a recent mammogram declined with increasing age, and the age association was independent of other factors including health status (adjusted odds ratio [OR] comparing women aged 75 years or older with those aged 50 to 64 years was 0.54; 95% confidence interval [CI] 0.41, 0.70). This age effect persisted in an analysis restricted to women reporting good or better health (adjusted OR was 0.60, 95% CI 0.44, 0.80). CONCLUSION: The observed decline in recent mammography use with advancing age was not explained by variation in health status. Because healthy elderly women may live long enough to realize the potential benefit of screening mammography, factors responsible for its reduced use should be identified. Doing so will allow for the selective promotion of screening mammography among those older women most likely to benefit.